Soil-Plant Interactions in the High-Altitude Ecosystems: A Case Study from Kaz Dağı (Mount Ida),Turkey - ÖZYİĞİT, İBRAHİM İLKER; SEVEROĞLU, ZEKİ (Springer, London/Berlin, 2015)
Anatolia is one of the richest lands in the world for the natural diversity of its flora and fauna, and has also been a cradle for great civilizations for centuries. The land sustains a unique biological and cultural diversity both in the region as well as on the global scale (Ozturk et al. 1996a , b ). It is located at the meeting point of four important floral regions, namely Europe in the Northwest, the Caucasus in the Northeast, Mediterranean in the West and the South, and Mesopotamia in the Southeast (Ozturk et al. 2008 , 2010a). Kaz Da , known in the history as Mount Ida, is one of the important sites in the country located in the north of Edremit in northwestern Anatolian part within the borders of the states of Çanakkale and Balkesir. The region has been a center of attraction for the settlers all through the ages because of its fertile soils, wetlands, underground resources, favorable climatic conditions, a premium destination for the ecotourism activities, as a recreation spot, as well as for its floral and faunal richness (Efe et al. 2008 , 2011a , b , 2012 ; Satl 2009 ; Uysal 2010 ; Uysal et al. 2011 , 2012 ). This diversity of the mountain has served and sustained the people around this area for centuries.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary